Standardising Visual Control Devices for Tsetse Flies: Central and West African Species Glossina palpalis palpalis - Kaba, Dramane; Zacarie, Tusevo; M'Pondi, Alexis Makumyaviri; Njiokou, Flobert; Bosson-Vanga, Henriette; Kröber, Thomas; McMullin, Andrew; Mihok, Steve; Guerin, Patrick (My University, 2014)
Background: Glossina palpalis palpalis (G. p. palpalis) is one of the principal vectors of sleeping sickness and nagana in Africa with a geographical range stretching from Liberia in West Africa to Angola in Central Africa. It inhabits tropical rain forest but has also adapted to urban settlements. We set out to standardize a long-lasting, practical and cost-effective visually attractive device that would induce the strongest landing response by G. p. palpalis for future use as an insecticide impregnated tool in area-wide population suppression of this fly across its range.
Methodology/Principal Findings: Trials were conducted in wet and dry seasons in the Ivory Coast, Cameroon, the Democratic Republic of Congo and Angola to measure the performance of traps (biconical, monoconical and pyramidal) and targets of different sizes and colours, with and without chemical baits, at different population densities and under different environmental conditions. Adhesive film was used as a practical enumerator at these remote locations to compare landing efficiencies of devices. Independent of season and country, both phthalogen blue-black and blue-black-blue 1 m2 targets covered with adhesive film proved to be as good as traps in phthalogen blue or turquoise blue for capturing G. p. palpalis. Trap efficiency varied (8–51%). There was no difference between the performance of blue-black and blue-blackblue 1 m2 targets. Baiting with chemicals augmented the overall performance of targets relative to traps. Landings on smaller phthalogen blue-black 0.25 m2 square targets were not significantly different from either 1 m2 blue-black-blue or blue-black square targets. Three times more flies were captured per unit area on the smaller device.
Conclusions/Significance:Blue-black 0.25 m2 cloth targets show promise as simple cost effective devices for management of G. p. palpalis as they can be used for both control when impregnated with insecticide and for population sampling when covered with adhesive film.